DOES THE INTEGRATED HEALTH POST HAVE CONTEXTUAL EFFECT ON EXCLUSIVE BREASTFEEDING? A MULTILEVEL EVIDENCE FROM KARANGANYAR, CENTRAL JAVA - ?Arub, Lathifah; Pamungkasari, Eti Poncorini; Dewi, Yulia Lanti Retno (Journal of Maternal and Child Health, 2020)
Background: Breastfeeding provides amazing benefits for the health of the child and the mother. WHO and UNICEF suggest a mother should be able to practice and maintain exclusive breastfeeding during the first six months of her baby's life. This study aimed to analyze contextal effect of integrated health post on exclusive breastfeeding.Subjects and Method: This was cross sectional study conducted in 25 integrated health posts (posyandu) in Karanganyar, Central Java, from August to September 2019. A sample of 200 nursing lactating mothers who had children aged 7 to 12 months was selected by stratified random sampling. The dependent variable was exclusive breastfeeding. The independent variables were maternal age, education, occupation, type of birth delivery, knowledge, attitude, family support, and social capital. The data were collected by questionnaire. The data were analysis by multilevel multiple logistic regression with Stata 13.Results: Exclusive breastfeeding increased with maternal age 20 to 34 years (b= 2.38; 95% CI= 0.62 to 4.15; p= 0.008), maternal education ?Senior high school (b= 1.64; 95% CI= 0.01 to 3.23; p= 0.049), good knowledge (b= 2.13; 95% CI= 0.41 to 3.86; p= 0.015), positive attitude (b= 1.67; 95% CI= 0.10 to 3.23; p= 0.036), strong family support (b= 1.58; 95% CI= 0.10 to 3.07; p= 0.036), and strong social capital (b= 1.64; 95% CI= 0.01 to 3.27; p= 0.049). Exclusive breastfeeding decreased with mother working outside the house (b= -3.54; 95% CI= -5.50 to -1.58; p<0.001) and sectio caesarea (b= -1.88; 95% CI= -3.58 to -3.58 to -0.19; p= 0.029). Integrated health post had strong contextual effect on exclusive breastfeeding with intra-class correlation (ICC)= 29.3%.Conclusion: Exclusive breastfeeding increases with maternal age 20 to 34 years, high maternal education, good knowledge, positive attitude, strong family support, and strong social capital. Exclusive breastfeeding decreases with mother working outside the house and sectio caesarea. Integrated health post has strong contextual effect on exclusive breastfeeding.Keywords: exclusive breastfeeding, multilevel analysis, posyanduCorrespondence: Lathifah ?Arub, Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta, Central Java 57126. Email: lathifah.arub17@gmail.com. Mobile: 085789212539Journal of Maternal and Child Health (2020), 5(1): 100-110https://doi.org/10.26911/thejmch.2020.05.01.11